(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
In recent years, solar energy devices have been widely introduced among renewable energy sources. In particular, the use of thermal and electrical properties of solar energy is considered promising. Solar panels are used to convert solar energy into electrical energy. Solar panels are made up of small solar cells. Solar cells have optical, electrical and thermal losses. This research work is devoted to improving the optical properties of solar cells. In this research work, studies were conducted using a double-sided sensitive solar cell.